Constructivist Practicies Through Guided Discovery Approach: The Effect on Students' Cognitive Achievements in Nigerian Senior Secondary School Physics - A.O. Akinbobola; F. Afolabi (University of Sofia, 2009)
The study investigated constructivist practices through guided discovery approach and the effect on students' cognitive achievement in Nigerian senior secondary school Physics. The study adopted pretest-posttest control group design. A criterion sampling technique was used to select six schools out of nine schools that met the criteria. A total of 278 students took part in the study; this was made up of 141 male students and 137 female students in their respective intact classes. Physic Achievement Test (PAT) with the internal consistency of 0.77 using Kuder-Richardson formula (21) was the instrument used in collecting data. The data were analyzed using Analysis of Covariance (ANCOVA) and t-test. The results showed that guided discovery approaches was the most effective in facilitating students' achievement in physics after being taught using a pictorial organizer. This was followed by demonstration while expository was found to be the least effective. Also, there exists no significant difference in the achievement of male and female physics students taught with guided discovery, demonstration and expository teaching approaches and corresponding exposure to a pictorial organizer. It is recommended that physics teachers should endeavor to use constructivist practices through guided discovery approach in order to engage students in problem solving activities, independent learning, critical thinking and understanding, and creative learning, rather than in rote learning and memorization.